Hypervalent iodine-mediated intramolecular alkene halocyclisation - Bansal, Charu; Ruggles, Oliver; Rowett, Albert C.; Lennox, Alastair J. J. (Beilstein Journal of Organic Chemistry, 2024)
The chemistry of hypervalent iodine (HVI) reagents has gathered increased attention towards the synthesis of a wide range of chemical structures. HVI reagents are characterized by their diverse reactivity as oxidants and electrophilic reagents. In addition, they are inexpensive, non-toxic and considered to be environmentally friendly. An important application of HVI reagents is the synthesis of halogenated cyclic compounds, in particular, the intramolecular HVI-mediated halocyclisation of alkenes using carbon, oxygen, nitrogen or sulfur nucleophiles. Herein, we describe the examples reported in the literature, which are organised by the different halogens involved and the internal nucleophiles.
Keywords: cyclisation; halogenation; heterocycles; hypervalent iodine; oxidation